A Mobile Health Behavior Intervention to Reduce Pain and Improve Health in Older Adults With Obesity and Chronic Pain: The MORPH Pilot Trial - Fanning, Jason; Brooks, Amber K.; Ip, Edward; Nicklas, Barbara J.; Rejeski, W. Jack; Nesbit, Beverly; Ford, Sherri (Frontiers in Digital Health, 2020)
Chronic, multisite pain is a common phenomenon in aging and is associated with a host of negative health outcomes. It is a complex and multifaceted condition that may be exacerbated by weight gain and long periods of inactivity. Unfortunately, older adults suffering from chronic pain have unique barriers limiting access to center-based behavior change interventions. The MORPH study first adapted and iteratively refined an evidence-based group-mediated intervention for delivery in the home via mHealth tools (a smartphone app, teleconferencing software, wearable activity monitor, smart weight scale). This was followed by a pilot randomized controlled trial (RCT) meant to assess feasibility and acceptability, and to examine initial effects on physical function, pain, weight, and sedentary behavior. We recruited low-active and obese older adults with multisite pain to partake in a series of N-of-1 refinement studies (N=5 total) or a 12-week pilot RCT delivered largely in the home (N=28 assigned to active intervention or wait-list control). The refinement phase identified several key technological (e.g., selection of a new smart weight scale) and user interface (e.g., clarification of in-app phrasing) modifications that were made before initiating the RCT phase. Analyses of covariance, controlling for baseline values, sex, and age, indicated effects favoring the intervention across all domains of interest: there was a substantially clinically meaningful difference in short physical performance battery scores (0.63 points, η^2=.08, a moderate-to-large difference in PROMIS pain intensity scores (5.52 points, η^2=.12), a large difference in body weight (2.90 kg, η^2=.207), and a moderate effect on adjusted ActivPAL-assessed sedentary time (64.90 minutes, η^2=.07) with a small effect on steps (297.7 steps, η^2=.01). These results suggest a largely-home delivered movement and weight loss program for older adults with pain is feasible, and recommendations are provided for future programs of this nature.